Sleepless In Seattle No Longer - Reich, Joshua; Goraczko, Michel; Kansal, Aman; Padhye, Jitu (USENIX Annual Technical Conference, 2010)
In enterprise networks, idle desktop machines rarely sleep, because users (and IT departments) want them to be always accessible. While a number of solutions have been proposed, few have been evaluated via real deployments. We have built and deployed a lightweight sleep proxy system at Microsoft Research. Our system has been operational for six months, and has over 50 active users. This paper focuses on providing a detailed description of our implementation and test deployment, the first we are aware of on an operational network. Overall, we find that our lightweight approach effected significant energy savings by allowing user machines to sleep (most sleeping over 50% of the time) while maintaining their network accessibility to user satisfaction. However, much potential sleep was lost due to interference from IT management tasks. We identify fixing this issue as the main path to improving energy savings, and provide suggestions for doing so. We also address a number of issues overlooked by prior work, including complications caused by IPsec. Finally, we find that if certain cloud-based applications become more widely adopted in the enterprise, more specialized proxy reaction policies will need be adopted. We believe our experience and insights will prove useful in guiding the design and deployment of future sleep solutions for enterprise networks.